A recepção do pensamento greco-romano árabe e judaico pelo ocidente medieval. Porto Alegre: EDIPUCRS, 2004. - Vasconcellos, Manoel L. (Veritas (Porto Alegre), 2004)
A recepção do pensamento greco-romano árabe e judaico pelo ocidente medieval.